Návrh trysky pro vysokotlaké tryskání - Šinágl, Viktor; Viktor Šinágl (České vysoké učení technické v Praze, 2020)
Tato bakalářská práce se zabývá návrhem trysky pro vysokotlaké tryskání, zejména pro tryskání úzkých štěrbin mostních konstrukcí. Teoretická část popisuje základní druhy předúpravy povrchu, podrobněji se zabývá mechanickou předúpravou povrchu a popisuje základní metody mechanické předúpravy povrchu a technologie tryskání, včetně vyhodnocení dosažené kvality povrchu po tryskání. V experimentální části se tato práce věnuje návrhem trysky pro vysokotlaké tryskání ze závěrů získaných z experimentálního ověření metod tryskání na mostě pod Vyšehradem, provedeném Fakultou strojní, Fakultou stavební a Kloknerovým ústavem Českého vysokého učení technického v Praze.

This bachelor thesis deals with the design of a nozzle for high pressure blasting, especially for blasting of crevasses on the bridge structures. The theoretical part describes the basic types of surface pre-treatment and deals with mechanical surface pre-treatment in more details. Basic methods of mechanical surface pre-treatment and blasting technologies are described, including the evaluation of the surface quality acquired from the blasting process. In the experimental part, this work deals with the design of a nozzle for high-pressure blasting based on the conclusions obtained during the experimental verification of several blasting methods, perfomed on the bridge under Vyšehrad by the Faculty of Mechanical Engineering, Faculty of Civil Engineering and the Klokner Institute of the Czech Technical University in Prague.
Nozzle design for high pressure blasting
Keywords: Vysokotlaké tryskání; tryskání; návrh trysky; tryskání mostních konstrukcí; High pressure blasting; blasting; nozzle design; blasting of the bridge structures